The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN